The Contribution of Moralist Leadership and Adhocracy Organizational Culture to the Performance of Public Elementary School Teachers in Lubuk Basung District - Irawati Irawati; Yahya Yahya; Rifma Rifma; Anisah Anisah (International Journal Labs, 2023)
The phenomenon found shows that the performance of public elementary school teachers in the Lubuk Basung sub-district is relatively low. It is suspected that the cause is moralist leadership and adhocracy organizational culture. This study aims to reveal whether the two factors of moralist leadership and adhocracy organizational culture contribute to the performance of public elementary school teachers in the Lubuk Basung sub-district. The hypotheses proposed in this study are: 1) Moralistic leadership contributes to teacher performance, 2) Adhocracy organizational culture contributes to teacher performance and 3) Moralist leadership and adhocracy organizational culture together contribute to teacher performance. The study population was 300 public elementary school teachers in Palembayan District. The sample was drawn using a stratified proportional random sampling technique. The selected sample was 90 people. To test the hypothesis, correlation, and regression analysis techniques were used. Data collection using a questionnaire that has been tested for validity and reliability. The results of data analysis show that: 1) Moralist leadership contributes 22.1% to teacher performance, 2) Adhocracy organizational culture contributes 19.7% to teacher performance and 3) Moralist leadership and adhocracy organizational culture together contribute 31.9% to teacher performance. The level of score achievement for these three variables (teacher performance, moralist leadership, and adhocracy organizational culture) is in a good category. The results of this study indicate that moralist leadership and adhocracy organizational culture are two factors that need to be applied by principals to improve the performance of public elementary school teachers in Lubuk Basung District.